INTEGRATED WEED MANAGEMENT IN BLACKGRAM (VIGNA MUNGO L.) AND ITS EFFECT ON SOIL MICROFLORA UNDER SANDY LOAM SOIL OF WEST BENGAL - RAJIB DAS; B. C. PATRA; M. K. MANDAL; ANIMESH PATHAK (The Bioscan, 2014)
The experiment was conducted in randomized block design (RBD) with 7 treatments in 3replications. Treatments comprised of T1 -Pendimethalin @ 1.5 lit/ha, T2 -Fluchloralin @ 1.5 lit/ha, T3 -Pendimethalin @ 1.5 lit/ha + hand weeding at 25 DAS, T4 -Fluchloralin @ 1.5 lit/ha + hand weeding at 25 DAS, T5 -Two hand weeding at 15 and 25 DAS,T6 -Weedy check. Result showed that T5 recorded lowest weed population (84.1 no/m2 and 55.5 no/m2) and dry weight (13.23 and 10.57 g/m2 ) which was significantly superior over rest of the treatments. Though weed control efficiency (85.53%) and seed yield (1.441 t/ha), stover yield (3.419 t/ha) were highest under treatment T5but net return per rupee investment (2.2) was highest under T3 as compared to other weed control treatments. There were no significant variations on the microbial population of the soil in the rhizospere region of the blackgram due to the application of testing herbicide.